2012
DOI: 10.1248/bpb.35.413
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Enzymes Responsible for the N-Oxidation of Darexaban Glucuronide, the Pharmacologically Active Metabolite of Darexaban, and the Glucuronidation of Darexaban N-Oxides in Human Liver Microsomes

Abstract: Darexaban maleate is a novel oral direct factor Xa inhibitor. Darexaban glucuronide (YM-222714) was the major component in plasma after oral administration of darexaban to humans and is the pharmacologically active metabolite. Additionally, YM-222714 N-oxides were detected as minor metabolites in human plasma and urine. It is possible that YM-222714 N-oxides are formed by the N-oxidation of YM-222714 and/or the glucuronidation of darexaban N-oxides (YM-542845) in vivo. The former reaction is the pharmacologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Notably, this statement remains true for states of potent CYP3A or P‐gp inhibition or induction. Based on several studies investigating the metabolic pathway of darexaban and darexaban glucuronide, the effect of CYP3A inhibition was expected to be small, since the main enzyme involved in the metabolism of darexaban is UGT1A which forms the active metabolite darexaban glucuronide as well as flavin‐containing mono‐oxygenase 3, which subsequently converts darexaban glucuronide into darexaban glucuronide‐ N ‐oxide . The involvement of CYP3A is limited to a very minor metabolic pathway where darexaban is converted into the metabolite YM‐228934 (data on file).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, this statement remains true for states of potent CYP3A or P‐gp inhibition or induction. Based on several studies investigating the metabolic pathway of darexaban and darexaban glucuronide, the effect of CYP3A inhibition was expected to be small, since the main enzyme involved in the metabolism of darexaban is UGT1A which forms the active metabolite darexaban glucuronide as well as flavin‐containing mono‐oxygenase 3, which subsequently converts darexaban glucuronide into darexaban glucuronide‐ N ‐oxide . The involvement of CYP3A is limited to a very minor metabolic pathway where darexaban is converted into the metabolite YM‐228934 (data on file).…”
Section: Discussionmentioning
confidence: 99%
“…Based on several studies investigating the metabolic pathway of darexaban and darexaban glucuronide, the effect of CYP3A inhibition was expected to be small, since the main enzyme involved in the metabolism of darexaban is UGT1A which forms the active metabolite darexaban glucuronide as well as flavin-containing mono-oxygenase 3, which subsequently converts darexaban glucuronide into darexaban glucuronide-N-oxide. 10,17 The involvement of CYP3A is limited to a very minor metabolic pathway where darexaban is converted into the metabolite YM-228934 (data on file). YM-228934 was not analysed in the current study, since it had been shown in previous human clinical pharmacology studies that at the dose darexaban 60 mg, the concentrations of YM-228934 are below the limit of quantification (data on file).…”
Section: Discussionmentioning
confidence: 99%